2020
DOI: 10.1186/s13071-020-04225-9
|View full text |Cite
|
Sign up to set email alerts
|

First molecular subtyping and phylogeny of Blastocystis sp. isolated from domestic and synanthropic animals (dogs, cats and brown rats) in southern Iran

Abstract: Background Blastocystis sp. is a common intestinal protist that infects humans and many animals globally. Thus far, 22 subtypes (STs) have been identified in mammalian and avian hosts. Since various STs are common to humans and animals, it was suggested that some human infections might arise from zoonotic transmission. Therefore, the aim of this study was to assess the presence of Blastocystis sp. in domestic (dogs and cats) and synanthropic animals (rats)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 75 publications
(160 reference statements)
5
23
1
Order By: Relevance
“…Blastocystis sp. has been identified in many animal hosts, such as NHPs, pigs, cattle, sheep, goats, dogs, birds, and various captive wildlife [ 23 , 24 , 33 ]. The prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blastocystis sp. has been identified in many animal hosts, such as NHPs, pigs, cattle, sheep, goats, dogs, birds, and various captive wildlife [ 23 , 24 , 33 ]. The prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Blastocystis sp. has been reported in a substantial number of animal hosts, including livestock, companion animals, and captive wildlife, with greatly varying prevalence [ 22 – 24 ]. In recent years, several important intestinal zoonotic pathogens (e.g., Cryptosporidium , Giardia , and Microsporidia) have been reported in captive wildlife in China [ 25 , 26 ], highlighting wildlife may be potential reservoirs for human to contract these infectious agents.…”
Section: Introductionmentioning
confidence: 99%
“…The authors examined totally 23 Blastocystis isolates from R. exulans and R. novercious, all were belonged to Blastocystis ST4. A study from southern Iran reported that 15.8% of rats were infected with Blastocystis and three subtypes were detected, including ST4, ST3, and ST1 (20). The distribution of Blastocystis subtypes was studied among symptomatic patients in Manisa and İzmir: ST3 (44.7%), ST1 (13.8%), ST2 (11.7%), ST6 (1%), ST7 (1.1%) and ST2+ST3 (2.1%) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Blastocystis sp. is a common enteric protist parasite of humans and animals [ 1 , 2 ]. It has a global distribution and is one of the most common human intestinal parasites in both developed and developing countries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%